Is It Stevens–Johnson Syndrome or MIS-C with Mucocutaneous Involvement?. (24th December 2021) - Karimi, Abdollah; Pourbakhtiaran, Elham; Fallahi, Mazdak; karbasian, Fereshteh; Armin, Shahnaz; Babaie, Delara
Abstract : Background . Severe acute respiratory syndrome coronavirus-2 (SARS-COV-2) can be present in the form of multisystem inflammatory disease in children. Case Presentation . A 25-month-old boy presented with fever, malaise, diffuse maculopapular rashes, and mucosal involvement during the COVID-19 pandemic. He was first diagnosed with Stevens–Johnson syndrome (SJS). Further evaluation revealed lymphopenia, thrombocytopenia, and elevated levels of C-reactive protein (CRP), ferritin, and fibrinogen. This was followed by a positive polymerase chain reaction (PCR) test for COVID-19. In addition to receiving initial care for SJS, he was treated for MIS-C, which led to his recovery after four days. Conclusion . COVID-19 infection should be considered in children with fever and dermatological features during the pandemic because it may cause different features of the multisystem inflammatory syndrome in children (MIS-C), suggestive of delayed hyperimmune response.